Utilizing social media to explore cultural tourism experiences at Al Jazeera Al Hamra Heritage Village - Dzamtoska-Zdravkovska, Suzana; Matlievska, Margarita; Petrevska, Biljana (International Journal of Innovative Research and Scientific Studies, 2025)
This research aims to explore and understand the visitor experiences at Al Jazeera Al Hamra, a significant heritage village in the United Arab Emirates recognized for its cultural importance and potential global value as reflected by its inclusion on the UNESCO World Heritage Cultural Tentative List. The study employs a qualitative research design utilizing manual content analysis. The data source comprises travelers’ reviews of Al Jazeera Al Hamra collected from TripAdvisor between July 2014 and January 2025. These reviews were systematically analyzed to identify recurring themes and patterns in visitor perceptions and experiences. The analysis of traveler reviews revealed four key dimensions that significantly shape the unique visitor experience at Al Jazeera Al Hamra: “Authentic,” reflecting the genuine historical atmosphere of traditional Emirati culture, architecture, and lifestyle; “Affective,” characterized by mildly to strongly positive emotional responses; “Cognitive,” indicating enjoyment derived from exploration and learning; and “Novel,” associated with the discovery of different and rare aspects of the heritage site. The "Authentic" dimension emerged as particularly dominant in shaping the overall experience, fostering a feeling of stepping back in time. The study concludes that the unique blend of authenticity, positive emotional engagement, cognitive enjoyment through exploration, and the novelty of discovery are central to the visitor experience at Al Jazeera Al Hamra. The genuine historical atmosphere is a key driver of positive perceptions. The findings suggest that tourism policymakers can leverage social media platforms, particularly TripAdvisor, as valuable sources of data on traveler experiences to identify key areas for promotion and management. To cultivate memorable experiences, a holistic and integrated approach is crucial. This necessitates the development of sustainable management strategies focused on preserving the village’s authenticity while strategically developing it as a cultural tourism destination. By understanding and emphasizing the identified experiential dimensions, policymakers can enhance marketing efforts and guide the sustainable development of Al Jazeera Al Hamra.